Edukasi Pencegahan Tbc Secara Dini Di Masyarakat Desa Sigi Kecamatan Kahayan Tengah Kabupaten Pulang Pisau - Mimin Lestari; Supriandi Supriandi (Journal of Midwifery in Community (JMC), 2024)
Pulmonary tuberculosis (pulmonary TB) is an infectious disease caused by the bacterium Mycobacterium tuberculosis. This disease remains a significant global health issue, with an estimated one-third of the world's population infected. The majority of pulmonary TB cases occur in individuals of productive age (15-50 years). In 2013, there were 9 million new cases and 1.5 million deaths attributed to pulmonary TB. Pulmonary TB is characterized by high morbidity and spreads easily through airborne droplets expelled by infected individuals. Therefore, immediate and careful treatment is essential when a case is detected in any area. Despite various control efforts reducing incidence and mortality, tuberculosis still affected an estimated 9.6 million people and caused 1.2 million deaths in 2014. India, Indonesia, and China have the highest number of TB cases, accounting for 23%, 10%, and 10% of global cases, respectively. The socio-economic environment, housing quality, and close contact with BTA+ hosts significantly influence the spread of this bacterium. Home environmental conditions, such as the presence or absence of ultraviolet light, adequate ventilation, humidity, house temperature, and occupancy density, are critical factors in the transmission of tuberculosis bacteria.